2021
DOI: 10.1002/brb3.2379
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuropathy: Two case reports of gasserian ganglion stimulation

Abstract: This report describes the successful treatment of two patients with trigeminal neuropathy by using gasserian ganglion stimulation. Case reports:The first case report deals with a 53-year-old woman suffering from right-sided facial pain after a gamma knife lesion for schwannoma of the right inner ear. For 9 years, several interventions with the aim of relieving the pain were unsuccessful; in fact, they had aggravated the symptoms. A trial with a neurostimulator at the level of the Gasser ganglion had an immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Nevertheless, it is difficult for patients to benefit from neuro-destructive surgery as classical TN does. 11 , 12 Because these treatments were poorly effective, 73% of patients experienced more severe pain symptoms after surgery. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is difficult for patients to benefit from neuro-destructive surgery as classical TN does. 11 , 12 Because these treatments were poorly effective, 73% of patients experienced more severe pain symptoms after surgery. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported undesirable outcomes where neuro-destructive interventions had little beneficial effect and exacerbated pain symptoms in 73% of patients ( 26 ). Furthermore, neuro-destructive surgery was also not recommended for patients with trigeminal neuropathy in other studies ( 19 , 20 ). The preferred and alternative forms of treatment for herpetic trigeminal neuralgia include neuromodulation techniques, such as pulsed radiofrequency, peripheral trigeminal nerve stimulation, or GGS.…”
Section: Discussionmentioning
confidence: 99%
“…First, the bipolar plate or 8-contact lead was being extensively applied in the treatment of trigeminal neuropathy at the level of Gasserian ganglion neuromodulation, but a high incidence of electrode dislocation and dysesthesia was reported. To solve the problem, Medtronic developed a custom-made tripolar-tined lead ( 19 , 20 ), but it was not available in China, which limited the use of this electrode. Second, if the trial stimulation was satisfactory, permanent electrode implantation was worth considering to ensure good pain control; however, this put a great financial burden on patients.…”
Section: Introductionmentioning
confidence: 99%
“…The TG, also known as the Gasserian ganglion, is a conjunction of all three trigeminal branches that permits one to designate precise facial areas based on the available somatotopic arrangement of nerve fibers while achieving a therapeutic effect on the full half of the face with minor surgical intervention. In refractory trigeminal neuropathy, stimulation of the Gasserian ganglion is an effective, minimally invasive, and non-destructive treatment that ought to be considered earlier in the treatment algorithm [ 31 ]. Despite a few risks, such as electrode dislocation (10–30%) and other mechanical defects (24%), TG electric stimulation has shown to be effective in treating patients with chronic trigeminal neuropathic pain and persistent idiopathic facial pain who have tried and failed or were not deemed candidates for standard surgical interventions [ 39 ].…”
Section: Trigeminal Ganglion Stimulation Approachesmentioning
confidence: 99%